Religion and Democracy in Argentina Religious Opposition to the Legalization of Abortion - Carbonelli, Marcos (Religions, 2023)
This article analyzes the ways in which religious actors opposing the legalization of abortion adjusted their arguments and public actions to the Argentine democratic culture between 2018 and 2020. Data were collected through a qualitative research approach by conducting in-depth interviews with activists, studying public position statements in secondary sources, and analyzing pronouncements and interactions on social media platforms. Religious agents conceived of democracy as the rule of the majority that they intended to promote by means of secular arguments, demonstrations in public spaces, and the construction of electoral alternatives. Marginally, the categorization of feminism through conspiracy theories and the use of dilatory legal maneuvers ran counter to the logic of the expansion of rights. According to the empirical evidence gathered, the religious agents showed increasing adjustments to the language and criteria inherent to democratic life.